Emerging Threat of Antimicrobial Resistance in β-Hemolytic Streptococci - Oppegaard, Oddvar; Skrede, Steinar; Mylvaganam, Haima; Kittang, Bård Reiakvam (Frontiers in Microbiology, 2020)
Highly variable resistance rates to erythromycin and clindamycin have been reported in the β-hemolytic streptococcal species Streptococcus pyogenes, Streptococcus agalactiae and Streptococcus dysgalactiae, depending on geographic and temporal context. In the present study we aimed to examine the longitudinal trends of antimicrobial resistance in these three species in a northern European setting. Furthermore, we used whole genome sequencing to identify resistance determinants and the mobile genetic elements involved in their dissemination, as well as elucidate phylogenetic relationships. All cases of invasive β-hemolytic streptococcal diseases in Health Region Bergen, western Norway, in the period 2004 to 2018 were retrospectively identified, comprising 271, 358 and 280 cases of S. pyogenes, S. agalactiae and S. dysgalactiae, respectively. Antimicrobial susceptibility testing revealed a gradual but significant increase in erythromycin and clindamycin resistance for S. agalactiae and S. dysgalactiae during the study period. Whole genome sequencing of the erythromycin and clindamycin resistant bacterial population revealed a substantial phylogenetic diversity in S. agalactiae and S. dysgalactiae. However, the mobile genetic elements harboring the resistance determinants showed remarkable intra- and interspecies similarities, suggesting a dissemination of antimicrobial resistance predominantly through conjugative transfer rather than clonal expansion of resistant strains in these two species. Conversely, antimicrobial resistance in S. pyogenes remained low, apart from a transient outbreak of a clindamycin and erythromycin resistant emm11/ST403-clone in 2010 – 2012. Increased epidemiological attentiveness is warranted to monitor the emerging threat of antimicrobial resistance in β-hemolytic streptococci, particularly in S. agalactiae and S. dysgalactiae.